One continuous fight : the retreat from Gettysburg and the pursuit of Lee's Army of Northern Virginia, July 4-14, 1863 - Wittenberg, Eric J., 1961- (Savas Beatie, 2008)
An account of what really happened following the Confederate retreat from Gettysburg. The book is a comprehensive study loaded with incisive tactical commentary, new perspectives on the strategic role of the Southern and Northern cavalry, and fresh insights on every engagement, large and small, fought during the retreat.